The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1136/sti.73.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B markers in heterosexual patients attending two genitourinary medicine clinics in the West Midlands.

Abstract: Objective: To determine the prevalence of hepatitis B virus (HBV) infection in heterosexual patients attending two genitourinary medicine (GUM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The prevalence in t 1 was similar to the 15.3% for British MSM recruited via outreach activities [24]. In HRPs, the anti-HBc prevalence was with 5.5% (t 1 ) and 4.5% (t 2 ), higher than the 0.8%-3.2% reported in heterosexual STI clinics visitors in other lowendemic countries [25,26]. This is in line with the high participation of ''swingers" in the HRPs, of whom it is known that they have a high STI prevalence [27].…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence in t 1 was similar to the 15.3% for British MSM recruited via outreach activities [24]. In HRPs, the anti-HBc prevalence was with 5.5% (t 1 ) and 4.5% (t 2 ), higher than the 0.8%-3.2% reported in heterosexual STI clinics visitors in other lowendemic countries [25,26]. This is in line with the high participation of ''swingers" in the HRPs, of whom it is known that they have a high STI prevalence [27].…”
Section: Discussionmentioning
confidence: 84%
“…This should be confirmed by studies that determine the country of birth and other risk factors of each individual. A study of heterosexual GUM clinic attenders in the West Midlands found a prevalence of past infection of 1n9 %, with most (15\28) positives born outside the UK [24]. Similar studies elsewhere would provide an upper limit on the risk of heterosexual infection in England and Wales.…”
Section: Discussionmentioning
confidence: 93%
“…Enhanced surveillance has suggested that obtaining more complete data would attribute a higher proportion of cases to sexual exposure [3], and therefore this increase may represent better recognition and reporting of this route of transmission. A survey amongst homosexuals in clinic and community settings found that 17 % had evidence of past HBV infection [26], whereas the prevalence of past infection was low in heterosexuals attending a GUM clinic outside of London [27]. National coverage of selective vaccination has not been determined but ad-hoc surveys suggest that coverage in GUM clinics is low [23,28,29].…”
Section: Discussionmentioning
confidence: 99%